تقييم النتائج العلاجية لكل من المترونيدازول جيل (%0.8)والإريثرومايسين جيل(%4) والبيموكروليموس كريم(1%) في التهاب الجلد حول الفم - معلا, محمد (Latakia University Journal -Medical Sciences Series, 2019)
شملت هذه الدراسة 120 مريض التهاب جلد حول الفم, وزعوا إلى ثلاث مجموعات ضمت كل مجموعة40 مريضاً. طبق المترونيدازول جيل(%0.8) لدى المجموعة الأولى مرتين يوميا ولمدة أربعة أسابيع ، بينما طبق الإريثرومايسين جيل(%4) لدى المجموعة الثانية، والبيموكروليموس كريم(%1) لدى المجموعة الثالثة بنفس الطريقة ولنفس الفترة الزمنية. تم إعادة التقييم السريري في اليوم: 22 , 15 , 8 أثناء العلاج وعند نهاية العلاج( اليوم 29). كما تم متابعة المرضى سريريا بزيارات دورية مرة كل شهر لمدة ستة أشهر بعد إيقاف العلاج. أظهرت دراستنا تفوقاً ملحوظاً للبيموكروليموس على كل من الإريثرومايسين والمترونيدازول في النتائج العلاجية وكذلك في المحافظة على هذه النتائج بعد انتهاء المعالجة. This study included 120 patients with perioral dermatitis, who were divided into three groups, each group included 40 patients. Metronidazole gel(0.8%) has been applied on the first group twice a day for 4 weeks, whereas erythromycin gel (4%) has been applied on the second group and pimocrolimus cream (1%) on the third; in the same way and for the same period. Clinical re-evaluation has been done at days: 8, 15,22 of treatment and at the end of treatment(day 29).We followed the patients clinically by regular visits monthly for 6 months after stopping treatment. Our study revealed that results of pimocrolimus were better than each of erythromycin and metronidazole in the treatment and stabilization after treatment of perioral dermatitis.